Observations of Public Bikesharing: Experiences from Ningbo, China. Issue 1 (2017) - Lu, Chenxi; Xu, Feifei; Dong, Sheng; Bie, Jing
This paper reports the experience of a bikeshare operation in Ningbo, China. For analysis of the characteristics of the system operation, system log data were collected for a month, and these data were supplemented by questionnaire data from 1, 856 respondents. It was found that the Ningbo bikeshare operation, when compared with that of other cities, had a higher car substitution rate of 16.1% and a higher public bike usage rate of 3.7 trips per bike per day. Together, these contributed to a higher than average reduction in car travel of 756.0 km per bike per year. Although the system was successful in terms of reduced car travel and user satisfaction, it still suffered from the problem of rent–return imbalance, especially during the morning and afternoon peak travel hours. It was also found that rainy weather discouraged the use of public bikes. Moreover, the survey showed that 70% of bike riders took bikes as the sole mode to reach their destination and only 30% of them used bikes as a "last mile" means to transfer to other transit modes. This factor is in contrast to the initial expectation that public bikes would mainly fulfill the last mile demand. It is suggested that the bikeshare system should be well planned, designed, and operated to cope with the negative effects of the imbalance problem and rainy weather conditions. The aim of the bikeshare system may need to be repositioned from a last mile solution to an independent public transportation system that supplements metro, bus, and taxi systems.